Demonstration of a high-speed electro-optic switch with passive-to-active integrated waveguide based on SU-8 material. Issue 55 (23rd May 2016) - Wang, Xi-Bin; Jiang, Ming-Hui; Sun, Shi-Qi; Sun, Jing-Wen; Yi, Yun-Ji; Chen, Chang-Ming; Sun, Xiao-Qiang; Wang, Fei; Cui, Zhan-Chen; Zhang, Da-Ming
Abstract : A Mach–Zehnder interferometer type of electro-optic switch with passive-to-active integrated waveguides was fabricated based on SU-8 material, which exhibited low insertion loss and high-speed switching response. Abstract : In this paper, a low-loss and high-speed Mach–Zehnder interferometer type of polymer electro-optic (EO) switch with a passive-to-active integrated waveguide was demonstrated. The characteristic parameters of the passive-to-active integrated polymer waveguide and the switch were carefully designed and simulated. The fabrication was done by using traditional semiconductor fabrication techniques such as spin-coating, photolithography, and wet etching. The switch was fabricated based on SU-8 material with the simple wet-etching procedure. The insertion loss of the passive-to-active integrated waveguide-based EO switch was improved from 12.3 dB to 7.7 dB compared to that of the only active waveguide-based EO switch. The measured switching rise time and fall time were 26.29 and 24.53 ns, respectively. This waveguide structure and the fabrication process are shown to be valuable for EO switches/modulators and planar active lightwave circuit applications.